A comparative study of anhedonia components between major depression and schizophrenia in Chinese populations - Li, Yinghui (Ann Gen Psychiatry, 2015)
BACKGROUND: Anhedonia is a prominent symptom of major depressive disorder (MDD) and schizophrenia. At present, it is believed that hedonic processing rather consists of the anticipatory and consummatory phase. The aim of this research is to explore the different anhedonia components in MDD and schizophrenia in Chinese populations. METHODS: A Chinese version of the Temporal Experience of Pleasure Scale (TEPS) was used to evaluate 176 MDD patients, 346 schizophrenia patients, and 268 healthy controls. Additionally, the 17-item Hamilton Depression Rating Scale (HAMD-17) was used for MDD patients, while the Positive and Negative Syndrome Scale (PANSS) was applied for schizophrenia. RESULTS: The scores of consummatory (TEPS-CON) and anticipatory pleasure (TEPS-ANT) in MDD and schizophrenia were both significantly lower than healthy controls (both P < 0.001). TEPS-CON and TEPS-ANT were negatively correlated with the score of HAMD-17, the duration of illness and admission times in MDD (P < 0.05 or 0.01). TEPS-CON was negatively related to PANSS total scores and negative symptoms (P < 0.05 or 0.01), but no significant correlation was found with duration of illness and admission times in schizophrenia (P > 0.05). There was no significant correlation between TEPS-ANT and any clinical variables (P > 0.05). CONCLUSIONS: The consummatory and anticipatory pleasures were both impaired in MDD and schizophrenia. Consummatory and anticipatory anhedonia can be considered as a “state” in MDD, but as a “trait” in schizophrenia.